Advanced water metering and its application in low income communities - Malunga, Masoabi (Water Research Group, 2017)
In South Africa, it is a legislative requirement that all water supply points be metered (van Zyl, 2011). Conventional meters are mostly used as the main means of monitoring water consumption by South African municipalities. In the last two decades, the water metering industry has seen substantial developments with new capabilities added to the conventional water meter, known as advanced meters. These advanced water meters have capability of processing, storing and communicating data without the need of human intervention. As such they come with desirable capabilities for both consumers and municipalities. These include prepaid meters which are special type of advanced water metering technology that is mostly applicable in the low income areas of South Africa. However, advanced water meters have significant drawbacks, such as higher failure rates (due to electronics, batteries and more components), higher purchase and maintenance costs and susceptibility to tampering. It is therefore necessary to make a conscious and informed consideration when deciding on which metering technology to implement for different users. This could be achieved through having a technology evaluation framework. The goal of this research was to develop an evaluation framework to help municipalities in the selection of appropriate advanced water metering technologies for application in low income communities. This goal was achieved through: determining the range of functionality of technologies both available and under development for advanced water metering; documenting case studies of both successful and failed implementation of advanced water meters, including social perception and impacts; developing an evaluation framework that can evaluate advanced water metering; and evaluating on technical, social, economic and environmental grounds. The results from literature and case studies indicate that in low income communities, advanced water metering is mainly implemented for cost recovery purposes. However, some municipalities implement advanced metering schemes for water management and debt recovery. The most advanced water metering technology being installed in low income communities is prepaid meters. Prepaid meters have a potential to fulfill all the range of objectives that municipalities install advanced metering technology for. This technology is found to have high maintenance requirements due to high failure rate. For successful implementation, it is important that municipalities have adequate budget for repairs and maintenance or seek technical support from manufacturers.